Patterns of endocrine reactivity in patients with recent myocardial infarction: Clinical and biochemical correlations: trial of endocrine therapy. Issue 5 (September 1970) - Ceremużyński, L.; Kuch, J.; Markiewicz, L.; Lawecki, J.; Taton, J.
Abstract : The following endocrine function parameters were studied serially in a group of 10 patients with recent myocardial infarction: blood and urinary levels of epinephrine and norepinephrine, urinary excretion of vanillyl-mandelic acid; protein-bound iodine, Hamolsky test ( Hamolsky, Stein, and Freedberg, 1957 ) ; blood insulin; 24-hour urinary excretion of 17-hydroxycorticoids, sodium, and potassium . The acute phase of myocardial infarction, especially in those patients with a severe clinical course ( rhythm disturbances, coronary insufficiency, circulatory failure ), was associated with disturbed endocrine reactivity . The most frequent and the earliest feature was the increased level of the 24-hour urinary excretion of epinephrine, combined with a pronounced decrease in blood insulin level. Later in the course of the disease, as the adrenergic reactivity returned to normal, there was an increase in blood insulin to normal levels. In 3 patients with severe clinical symptoms of acute myocardial infarction, there were, in addition to the increased 24-hour urinary excretion of catecholamines, a decreased blood insulin, higher than normal levels of protein-bound iodine, and of the Hamolsky test. One of these patients developed hypoadrenia. It is possible that the abnormal endocrine reactions accelerate the catabolic processes within cardiac tissue ( catecholamines, thyroid hormones ), especially when there is a possible functional deficiency of hormones, occurring as a general adaptation reaction to stress ( cortisol, insulin ). The disturbances that follow may be dangerous for the patient .